Efektivitas Hasil Fermentasi Limbah Kulit Durian (Durio zibethinus Murr) sebagai Reagen Alternatif dalam Pemeriksaan Protein Urine - Nizar, Mardyana; Jihan, Selviana Ramadhan; Citra, Trisna; Eros, Tresnawati (Universitas Mohammad Husni Thamrin, 2025)
The presence of proteinuria indicates glomerular permeability abnormalities.Urinary protein examination 6% acetic acid method is commonly used with commercial corrosive reagents, in its use must be cautious because it can cause burns, permanent damage to the eyes, and irritation of the mucous membranes. The use of acetic acid, such as vinegar, is not high-risk. The acid acetate, which can be used in urine protein testing, can be produced through a substance considered to be a waste, the durian skin. In durian skin contains carbohydrates with a huge 60-70% and still can be utilized. The aim of this study is to find out if there is any difference in the use of reagents resulting from the fermentation of durian leather waste with 6% commercial acetic acid as well as to know its effectiveness. Through liquidification, sacharization and aerobic, anaerobic fermentation processes assisted by the α-amilase enzyme, as well as the microorganisms Saccharomyces cerevisiae and Acetobacter aceti are able to produce acetic acid for urine protein testing by the method of acetate acid by heating. Reagents resulting from the fermentation of durian leather waste concentrations of 2.5%, 5%, 7.5% and 10% effective. Acetate acid levels measured by the method of titration of alkalimetry, the lowest rate at the concentration of 2.5% is 4.3% and the highest at the 10% concentration produces 5%. The research found that reagents derived from the fermentation of durian peel waste at concentrations of 2.5%, 5%, 7.5%, and 10% are effective for use as reagents in urine protein examination. Based on the statistical tests Kruskal Wallis came to the conclusion that there was no difference between the results of the test of urine protein using acetic acid results from fermenting durian skin waste with 6% commercial acetate. Keywords: Acetic Acid, Durian Skin, Titration, Urine